Autism spectrum disorder diagnosis using a new panel of immune- and inflammatory-related serum biomarkers: A case-control multicenter study - Gesundheit, Benjamin; Zisman, Philip David; Hochbaum, Leah; Posen, Yehudit; Steinberg, Avraham; Friedman, Gerald; Ravkin, Hersh D.; Rubin, Eitan; Faktor, Ouriel; Ellis, Ronald (Frontiers in Pediatrics, 2023)
Background and Objectives: Children with autism spectrum disorder (ASD) present with distinctive clinical features. No objective laboratory assay has been developed to establish a diagnosis of ASD. Considering the known immunological associations with ASD, immunological biomarkers might enable ASD diagnosis and intervention at an early age when the immature brain has the highest degree of plasticity. This work aimed to identify diagnostic biomarkers discriminating between children with ASD and typically developing (TD) children. Methods: A multicenter, diagnostic case-control study trial was conducted in Israel and Canada between 2014 and 2021. In this trial, a single blood sample was collected from 102 children with ASD as defined in Diagnostic Statistical Manual of Mental Disorders (DSM)-IV (299.00) or DSM-V (299.00)) and from 97 typically developing control children aged 3-12 years. Samples were analyzed using a high-throughput, multiplexed ELISA array which quantifies 1000 human immune/inflammatory-related proteins. Multiple logistic regression analysis was used to obtain a predictor from these results using 10-fold cross validation. Results: Twelve biomarkers were identified that provided an overall accuracy of 0.82±0.09 (sensitivity: 0.87±0.08; specificity: 0.77±0.14) in diagnosing ASD with a threshold of 0.5. The resulting model had an area under the curve of 0.86±0.06 (95% CI: 0.811 – 0.889). Of the 102 ASD children included in the study, 13% were negative for this signature. Most of the markers included in all models have been reported to be associated with ASD and/or autoimmune diseases. Conclusions: The identified biomarkers may serve as the basis of an objective assay for early and accurate diagnosis of ASD. In addition, the markers may shed light on ASD etiology and pathogenesis. It should be noted that this is only a pilot, case-control diagnostic study, with a high risk of bias. The findings should be validated in larger prospective cohorts of consecutive children suspected of ASD